Croire ensemble. Analyse institutionnelle du paysage religieux en Suisse - Monnot, Christophe (Seismo, 2013)
The study presented in this book for the first time in Switzerland offers a broad empirical and sociological perspective on local religious organizations. From this perspective, religion appears first, as already observed by Weber and Durkheim, through communities regardless of their various profiles. In Switzerland, 5,734 parishes and religious groups have been identified by a national census in 2008. The book underlines the institutional salience of historical churches (Reformed and Roman Catholic) but also the emerging religious plurality, particularly in urban areas. This study sheds a new light upon the effects of secularization (lower limbs and practice) and pluralisation (diversification of religious denominations and traditions) in the organizational field. The analysis of differences and similarities between religious traditions shows a social positioning of the local groups according to the statutes acquired in history. The classical theories − e.g. about the relationship between social status of members and membership groups, types of religious authorities or differences between Church and Sect − are revisited, clarified or reformulated based on an original and representative quantitative data of the Swiss religious field.